A Critical Review of the Book Wittgenstein on Rules and Private Language - Shahram Shahryari (پژوهش‌نامۀ انتقادی متون و برنامه‌های علوم انسانی)
Saul Kripke’s Wittgenstein on Rules and Private Language offers an unorthodox interpretation of Wittgenstein’s Philosophical Investigations. Contrary to other commentators, Kripke regards rule-following as the main issue of the book so that it gives Wittgenstein’s most significant argument for the impossibility of private language. Kripke formulates Wittgenstein’s argument in response to a skeptic who seeks a fact in exchange for the words’ meaning or correct rule-followings. Kripke’s Wittgenstein dismisses such a claim, arguing that the use of a word or following a rule is called “correct” when it agrees with other users of the language or rule. There is no corresponding fact for meaning or rule-following, nor is there any other criterion that can assess one’s responses. Kripke’s interpretation of Wittgenstein’s question and answer has provoked many philosophical debates, which have important implications for the methodology of the social sciences as well as the humanities. After an account of Kripke’s skeptical challenge and his answer to it, this paper reviews some rival interpretations and their criticisms of Kripke’s exegesis. This provides the opportunity to point out the impact of this debate on other intellectual issues. Finally, one of the Persian translations of this book will be examined.